One last promise [large type] - Warren, Susan May, 1966- (Warren, Susan May, 1966- Alaska Air One Rescue, 2024)
"After years as a pilot of a Navy rescue chopper, Arlo 'Moose' Mulligan returned home to start Air One Rescue--and made a name for himself. He loves his job, his life, and his routines, which include breakfast at the Skyport Diner, always at one of Tillie Young's tables. She's sweet and pretty, but Moose knows his life has no room for anything more. Until the day Tillie shows up beaten and desperate and needing his help. Tillie Young never thought her unhinged ex-trainer would track her to Alaska, but somehow he's found her. When he kidnaps her daughter, Tillie will do anything to get her child back--even enlist help from her favorite grumpy customer. But Moose Mulligan is no match for a former MMA boxer and possible child trafficker, right? Maybe, maybe not, but he's not going to let another child go missing on his watch. He must find the girl, keep Tillie safe, and outwit a man fueled by revenge. It will take all of Moose's Alaskan savvy to keep them alive--but who is going to protect him from the love he never saw coming?" --